Unsupervised mobile cognitive testing for use in preclinical Alzheimer's disease. Issue 1 (30th September 2021) - Papp, Kathryn V.; Samaroo, Aubryn; Chou, Hsiang‐Chin; Buckley, Rachel; Schneider, Olivia R.; Hsieh, Stephanie; Soberanes, Daniel; Quiroz, Yakeel; Properzi, Michael; Schultz, Aaron; García‐Magariño, Iván; Marshall, Gad A.; et al.
Abstract: Introduction: Unsupervised digital cognitive testing is an appealing means to capture subtle cognitive decline in preclinical Alzheimer's disease (AD). Here, we describe development, feasibility, and validity of the Boston Remote Assessment for Neurocognitive Health (BRANCH) against in‐person cognitive testing and amyloid/tau burden. Methods: BRANCH is web‐based, self‐guided, and assesses memory processes vulnerable in AD. Clinically normal participants (n = 234; aged 50–89) completed BRANCH; a subset underwent in‐person cognitive testing and positron emission tomography imaging. Mean accuracy across BRANCH tests (Categories, Face‐Name‐Occupation, Groceries, Signs) was calculated. Results: BRANCH was feasible to complete on participants' own devices (primarily smartphones). Technical difficulties and invalid/unusable data were infrequent. BRANCH psychometric properties were sound, including good retest reliability. BRANCH was correlated with in‐person cognitive testing ( r  = 0.617, P  < .001). Lower BRANCH score was associated with greater amyloid ( r  = –0.205, P  = .007) and entorhinal tau ( r  = –0.178, P  = .026). Discussion: BRANCH reliably captures meaningful cognitive information remotely, suggesting promise as a digital cognitive marker sensitive early in the AD trajectory.